Dimensión vertical de la región anterior de la mandíbula - Bolini, Paulo Domingos André [UNESP]; Gaspar, Ana Maria Minarelli; De Souza, Juliana Feltrin [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2006)
We made some measurements from the region of the symphysis menti in 308 dried mandibles; 247 belong to the collection of the cranial museum of the discipline of Anatomy of the UNIFESP- Escola Paulista de Medicina- EPM and 61 belong to the didactic laboratory of the discipline of Anatomy from the Faculdade de Odontologia de Araraquara- UNESP, Brasil. On the dentate mandibles, the highest value founded was of 43,46 mm and the lowest of 22,67 mm. On the edentate mandibles, the highest value founded was of 37,24 mm and the lowest of 6,22mm. We hope that with the following discoveries we could contribute to a better knowledge of the symphysis menti region, not only to the professionals in Surgery and Implantology areas, but the industrials of related areas, to the confection of instruments used in these practices. © 2007 Sociedad Chilena de Anatom•br>.
Vertical dimension in the anterior region of the mandible
Keywords: Anatomy; Mandible; Symphysis menti